Pengaruh Profitabilitas, Leverage, Corporate Governance, Dan Cash Holding Terhadap Nilai Perusahaan ( Studi Empiris Pada Perusahaan Aneka Industri Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2020-2022 ) - Mahindra Nathan Mastroyanna Arifin; Listyorini Wahyu Widati; Muhammad Ali Ma'sum (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study is to determine the effects of cash holding, corporate governance, profitability, and leverage on a company's value. In this study, quantitative methods are used. An industrial sector business that was listed on the Indonesian stock exchange between 2020 and 2022 serves as the sample. 126 samples were obtained by applying the purposive sample method to data extracted from the financial accounts. Data analysis techniques include double linear regression analysis and hypothesis testing (t-testing). The findings indicate that the following factors raise a company's value: cash holding, corporate governance, profitability, and leverage.